Análise dos acidentes de trabalho conforme as NR’s 6 E 7 em obras na cidade de Mossoró/RN - Barros, Liandra Samara Costa (Universidade Federal Rural do Semi-Árido, 2019)
The civil construction sector has great relevance to the Brazilian economy, since it is responsible for generating jobs and income, and for presenting a production chain associated with many other segments. However, it has serious weaknesses related to the qualification of employees and the occurrence of accidents in the workplace. Thus, this study aims to analyze compliance with Regulatory Standards 6 and 7, in construction works located in the city of Mossoró/RN. To this end, visits were made on site, which allowed the application of a checklist and photographic records. Bibliographic searches and consultations with the regulatory norms were also made. It was found that no work fully met the items analyzed. So, the best and worst work was 03 and 04, respectively. Regarding the Occupational Health Medical Control Program, no work even partially complied with the items consulted, showing directly the absence of preventive practices on the construction sites and the lack of care with the health, well-being and quality of work. workers' lives. This confirms a lack of supervision, which contributes to the perpetuation of neglect with work safety.
Monografia
Keywords: Construção civil; Segurança do trabalho; Norma Regulamentadora nº 6; Norma Regulamentadora nº 7; Construction; Workplace safety; Regulatory Standard nº 6; Regulatory Standard nº 7; ENGENHARIAS::ENGENHARIA CIVIL